Strategies for SMEs in Managing Big Data for Personalization and Customer Service Enhancement - Handayati, Ratna; Haliza, Siti Nur; Haqqoh, Arinil; Kumalasari, Endah Nur; Saputra, Yangga (ADMAN: Journal of Contemporary Administration and Management, 2024)
In the current digital era, big data has become an invaluable asset for various organizations, including Small and Medium Enterprises (SMEs). Big data refers to vast and complex datasets that cannot be managed or analyzed using traditional methods. This study aims to provide practical guidelines for SMEs on how they can efficiently and effectively manage big data for personalization and customer service enhancement. The research employs a literature review method with a qualitative approach, gathering data from Google Scholar covering the period from 2014 to 2024. The findings highlight how SMEs can leverage big data to improve personalization and customer service. Big data, characterized by its volume, velocity, and variety, offers significant opportunities for SMEs to understand customer preferences, enhance their experiences, and improve services. Despite facing challenges in terms of resources and skills, SMEs can overcome these hurdles by utilizing cloud-based technologies, affordable analytical tools, and skills training. Case studies such as Tinkr, Tokopedia, and Gojek illustrate how data analysis can enhance the relevance of product and service offerings, while challenges like data security and infrastructure limitations remain important issues to address.